O caso Santa Maria na TV: narrativa contemporânea como semiose - Debiasi, Carlos Alberto (2014)
This work investigates elements of contemporary journalistic narrative present in television programming and discusses the hybrid character of communication technologies . From the analysis of programs that depict the tragedy that took place in the city of Santa Maria in January 2013,semiotic and analytical bases are used in order to include common reference by which this type of communication operates in the transmission of messages on reality . It brings as a result the evidences of representation strategies within the analyzed cut. The conclusion serves as evidence of the constant reaffirmation of general discourse about social phenomena, reissued in new technological basis.